Musykilaat Ta'allum al-Lughah al-'Arabiyyah bi al-Madrasah al-Mutawassithah al-Islamiyyah Nurul Mujtahidin Mlarak Ponorogo - Leila Ahya Husnaya; Rizka Eliyana Maslihah (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
Learning Arabic is learning a foreign language, the main problem in learning Arabic is releated to the seriousness of student learning, and the teacher teaching. Learning Arabic with it’s characteristics makes it difficult for students because Arabic is not an easy language to master overall. And most people think that learning Arabic only the sake of religion. Then this is what cause students to experience difficulties or problems in Learning Arabic. From this background the objectives of this study: to know problem of learning Arabic, factors causing and solution to overcome the problem. This type of research is qualitative research. Researcher conducted research in Islamic Junior High Schools “Nurul Mujtahidin” Mlarak Ponorogo. The result of this study are: (1) that students experience problems learning Arabic which includes: difficulty in understanding and memorizing vocabulary, difficulty in speaking, difficulty in reading, difficulty in writing, difficulty in grammar Arabic, and difficulty in transliting. (2) as for the factors that cause students problems in learning Arabic are the internal factors of student which include affective, cognitive, and psychomotor aspect. While eksternal factors include family, community, and school factors. (3) as for the solution to overcome the problem of learning Arabic form Arabic teachers and schools use a variety of methods including: memorizing vocabulary, giving assignments and exercises, practicing writing with the method imla’. Carrying out support activities such as doing reading the Qur’an every month and also always giving motivation. While schools also implement oral examinations relating to Arabic and daily worship practices. الملخص تعليم اللغة العربية كاللغة الأجنبية تؤدي إلى ظهور المشكلات في تعلّمها، خاصة لطلاب هذه اللغة ومعلّمها. وظهرت المشكلات في تعلّم هذه اللغة لأنّ تعلّم اللغة العربية ليست من الأمر التّافه. ومن ثم تيقّن الطلاب أنّ تعلّم اللغة العربية هي نوع من تعليم علوم دين الإسلام. فيشعر الطلاب بصعوبة تعليم هذه اللغة، وها هي ذا مصدر المشكلات في تعلّم اللغة العربية عند الطلاب. وبالإضافة إلى هذه المشكلة، فتهدف كتابة هذه المقالة لأجل معرفة مشكلات الطلاب وتحليل عن الأسباب وطريقة حلّ هذه المشكلات. وكتبت هذه المقالة باستخدام منهج البحث النوعي، وميدان البحث هو المدرسة المتوسطة الإسلامية نور المجتهدين ملاراك فونوروغو. وأما النتائج لـهذه المقالة هي كما يلي: 1) يواجهون الطلاب المشكلات حسب المهارة اللغوية الأربعة ومنها: المشكلات في حفظ وفهم وتنفيذ المفردات، والمشكلات في مهارة الكلام، والمشكلات في مهارة القراءة، والمشكلات في مهارة الكتابة، والمشكلات في فهم القواعد اللغوية، والمشكلات في الترجمة. 2) عوامل الأسباب في مشكلات تعلّم الطلاب منها: العوامل الداخلية للطلاب من جانب المعرفي ومن جانب الوجداني متعلقة برغبة ودوافع الطلاب عند التعلّم. وأما لـجانب النفس الحركي هو بسبب المرض، والإعاقة الجسدية، أو تشوهات الحسية. 3) ولحلّ مشكلات الطلاب منها: يجب على الطلاب أن يحفظ سائر المفردات الجديدة ثمّ تطبيقها في الحوار. ويعطي المدرّس الواجب المنزلي لقراءة النصّ، وفي تعليم القواعد يترجم المدرّس النّص إلى اللغة الإندونيسية ومقارنتها، ثمّ يعطى الواجب المنزلي لترجمة النص. ثمّ يعطي المدرس الدوافع للطلاب.